MOLEKULER DOCKING DAN ANALISIS ADMET SENYAWA ANREDERA CORDIFOLIA TERHADAP DPP-4: OBAT DIABETES - Rahayu, Feri Kanti (Parapemikir : Jurnal Ilmiah Farmasi, 2025)
Diabetes is a degenerative disease characterized by hyperglycemia. Treatment of type 2 DM usually uses synthetic drugs that have side effects such as sulfonyl urea, biguanine, alpha-glycosidase drugs. Dipeptidyl Peptidase 4 (DPP4) enzyme inhibitor drugs have not been widely studied and have potential for hypoglycemia. This research aims to examine compound isolates from the binahong plant in inhibiting the DPP4 enzyme. The in silico method via molecular docking is the most relevant method in efforts to discover new drugs. Molecular docking is carried out through several stages including modeling and optimization of compound structures, preparation of target proteins and ligands, validation of docking, docking processes, and visualization of interactions and ADMET analysis. The research results show that of the 11 binahong plant compounds there are 3 compounds that have antidiabetic potential, namely 2,3-dihydroxypropyl palmitate, Squale and Linoleic acid, methyl ester with bond energy values respectively -104.1; -101.2; and 90.9 kcal/mol. ADMET analysis of 11 binahong plant compounds shows that the majority of compounds are absorbed through the gastrointestinal tract, distributed and metabolized with the help of the CYP1A2 enzyme and all compounds are not carcinogenic and not mutagenic. Based on the results of this research, it can be concluded that the compounds, namely 2,3-dihydroxypropyl palmitate, Squale and Linoleic acid, methyl ester can inhibit the DPP-4 enzyme and are not toxic so they have the potential to be antidiabetic.